S2: Active volcanoes in Marie Byrd Land - N.W. Dunbar; N.A. Iverson; J.L. Smellie; W.C. McIntosh; M.J. Zimmerer; P.R. Kyle (2021)
Map of Mount Waesche englacial tephra layers showing sample numbers. Exact GPS locations can be found in Supplementary material S1.